Diseño de una máquina dispensadora automatizada y de almacenaje de láminas metálicas - Barboza-Gamboa, Mauricio Esteban (Instituto Tecnológico de Costa Rica, 2017)
Eaton Electrical is a company consolidated worldwide for the production of electrical equipment, in Costa Rica the company has been since 1986. One of the main processes in the plant of Eaton Electrical SA in Costa Rica is the work in iron sheets for the formation of load centers. In the last five years the company has been concerned about investing in modernizing their equipment to improve productivity rates and delivery times, however, the new equipment despite its high production speeds do not have a process that benefits the yields of the machines. At the plant there are currently two CNC punchers that are the main ones affected by the process deficiencies, which register approximately 15% of the total work time in unemployment due to material waiting time-out. The proposed solution to this problem is the design of an automated sheet dispensing machine that can supply the need for sheets of each of these punchers throughout the entire day process. For the design of the mechanism, theories of failure by static loads (Tresca) and theories of failure by dynamic loads (by fatigue) are taken into account for the sizing of the components of the machine. For the selection of the structural profiles and other mechanical parts proper of the machine, a valuation of the national market is made in order to have all the materials. Once the necessary materials for each of the parts of the mechanism are selected, construction drawings are developed with the details with the help of SolidWorks software. The mechanical drawings indicate the adjustments of the pieces, characteristics of welds and dimensions of the pieces in each part respectively. As expected for the machine to have a full and automated operation will require electrical components. A list of electrical materials is generated to operate the machine and a connection diagram of the different equipment. In the case of electrical components, the Eaton Electrical brand's equipment is given top priority when making the choice, only non-Eaton equipment will be used when an equipment that can ensure the equipment is not within the possibilities, correct functioning or the characteristics sought. As part of the project the construction of the machine is supported through a financial analysis with tools such as VAN and ROI, which due to the high ratings of downtime are satisfactory.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2017.
Keywords: Diseño; Eaton Electrical; Productividad; Rendimiento; CNC´s; Research Subject Categories::TECHNOLOGY::Engineering mechanics::Mechanical manufacturing engineering